2021
DOI: 10.1038/s41398-020-01144-2
|View full text |Cite
|
Sign up to set email alerts
|

Lower amygdala fatty acid amide hydrolase in violent offenders with antisocial personality disorder: an [11C]CURB positron emission tomography study

Abstract: Antisocial personality disorder (ASPD) imposes a high societal burden given the repetitive reactive aggression that affected individuals perpetrate. Since the brain endocannabinoid system (ECS) has been implicated in ASPD and aggressive behavior, we utilized [11C]CURB positron emission tomography to investigate fatty acid amide hydrolase (FAAH), an enzyme of the ECS that degrades anandamide, in 16 individuals with ASPD and 16 control participants. We hypothesized that FAAH density would be lower in the amygdal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…The amygdala region is broader in ciswomen with a higher estrogen density than androgen receptors (Halpern, 2013). Furthermore, as we saw, the amygdala mediates empathy (Kolla et al, 2021) and empathy inhibits aggression (Decety & Lamm 2006). Yet, according to Gina Rippon (2019), nobody knows for certain whether having a bigger amygdala [or putamen] makes you more or less aggressive.…”
Section: Aggressionsupporting
confidence: 57%
See 2 more Smart Citations
“…The amygdala region is broader in ciswomen with a higher estrogen density than androgen receptors (Halpern, 2013). Furthermore, as we saw, the amygdala mediates empathy (Kolla et al, 2021) and empathy inhibits aggression (Decety & Lamm 2006). Yet, according to Gina Rippon (2019), nobody knows for certain whether having a bigger amygdala [or putamen] makes you more or less aggressive.…”
Section: Aggressionsupporting
confidence: 57%
“…Behaviors related to reproduction are recognizable in both parents in the levels of responses such as sociability, attachment, sentimentality (Stam, Huang, & Van den Stock, 2019), aggression (Zell et al, 2015), in defend or befriend (Hoekzema et al, 2015;Sokolowski & Corbin, 2012;McCarthy et al, 2012;Pearson et al, 2009;Zietsch et al, 2008), instinct (Sweatt et al, 2013), and significantly in empathy (Swain et al, 2007). Others have presented similar claims (see Kolla et al, 2021;Zaidi, 2010;Decety & Lamm 2006).…”
Section: Care Of Offspringmentioning
confidence: 94%
See 1 more Smart Citation
“…Using [ 11 C]CURB positron emission tomography (PET), we reported that FAAH expression was elevated in the prefrontal cortex (PFC) of BPD and that PFC FAAH density correlated with measures of anger/hostility 23 . Conversely, we also found utilizing [ 11 C]CURB PET that amygdala FAAH expression was lower in the amygdala of ASPD and that impulsive behaviors were negatively associated with FAAH density in other brain regions studied 24 . These findings have enhanced our knowledge about the pathophysiology of BPD and ASPD and their symptom clusters, yet an unanswered question remains how FAAH expression may relate to personality traits such as neuroticism.…”
Section: Introductionmentioning
confidence: 51%
“…We have previously reported neuroimaging data on a subset of these participants. However, the research questions and analyses for the present investigation were different from those of the previous studies 23 , 24 . BPD participants were primarily female ( n = 18), while all ASPD subjects were male.…”
Section: Methodsmentioning
confidence: 62%